The Incidence and Impacts of Student Transiency in Upstate New York's Rural School Districts - Kai A. Schafft (Journal of Research in Rural Education, 2005)
Chronic student mobility, and in particular the mobility of students from low-income backgrounds, poses a serious yet underdocumented problem for rural schools. This article combines analyses of state-level school district data with survey and interview data to examine the patterns of low-income student mobility in upstate New York, and to assess the impacts on, and responses by, schools and other community institutions. The incidence and effects of student mobility are particularly pronounced in smaller, limited-resource districts. School district administrators report significant negative consequences due to the fiscal and administrative costs associated with high-need, highly mobile students. Student transiency not only requires extra administrative resources from teachers, guidance counselors, and other school staff, but the unpredictability of the movement vastly complicates planning and budgeting processes. Results portray a significant, high-need segment of the upstate New York population that is largely unrecognized, untargeted, and both socially and academically at risk.